Killing Discarded Embryos and the Nothing‐is‐Lost Principle. (1st August 2013) - Devolder, Katrien
Abstract : A widely held view holds that it is permissible to conduct destructive research on embryos discarded following fertility treatment, but not on embryos especially created for research. One argument in support of this view appeals to the nothing‐is‐lost principle. It holds that because discarded embryos will die soon in any case, and something good is expected to come out of using them for research, it is presumptively permissible to do so. It is then claimed that no equivalent justification can be adduced in support of destructive research on embryos especially created for research. I argue that, on a standard formulation of the nothing‐is‐lost principle, this argument fails. I consider whether other plausible variants of the principle render the argument sound and argue that they do not.